Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppression; thématiques; travail; états-unis

Margaret Thatcher is my sister: Counselling on divisions between women - Itzin, Catherine (Women's Studies International Forum, 1985)
This paper looks at the ways in which women are divided from themselves and each other as women: at the internalised oppression which results from THE oppression of patriarchy, at the systematic mistreatment of women as a group by men as a group reinforced by the social structures of male power. It also looks at the ways in which women are divided from each other as a result of other oppressive systems such as class and/or race or religion or physical ability or age. The paper then describes how the particular theory and practice of Re-evaluation Counselling can be used to ‘deconstruct’ or ‘discharge’ the internalised oppression of patriarchy and other oppressive systems, making the principles of Women's Liberation and sisterhood a practical possibility for ‘everywoman’ and all women—including Margaret Thatcher. Throughout, the word ‘patriarchy’ is used to mean the system of male power usually regarded as synonymous with sexism.
Keywords: approches et analyses; capacitisme; militance; patriarcat; racisme; sororité; systèmes d'oppression; thématiques; âgisme